A measurement of the ratio of the production cross sections for [Formula: see text] and [Formula: see text] bosons in association with jets with the ATLAS detector. - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Abreu, R; et al. (2014)
The ratio of the production cross sections for [Formula: see text] and [Formula: see text] bosons in association with jets has been measured in proton-proton collisions at [Formula: see text] with the ATLAS experiment at the Large Hadron Collider. The measurement is based on the entire 2011 dataset, corresponding to an integrated luminosity of [Formula: see text]. Inclusive and differential cross-section ratios for massive vector bosons decaying to electrons and muons are measured in association with jets with transverse momentum [Formula: see text] and jet rapidity [Formula: see text]. The measurements are compared to next-to-leading-order perturbative QCD calculations and to predictions from different Monte Carlo generators implementing leading-order matrix elements supplemented by parton showers.